2024
DOI: 10.3389/fonc.2024.1362641
|View full text |Cite
|
Sign up to set email alerts
|

Sacituzumab Govitecan for the treatment of advanced triple negative breast cancer patients: a multi-center real-world analysis

Roberta Caputo,
Giuseppe Buono,
Michela Piezzo
et al.

Abstract: ObjectiveThe objective of this multicenter, observational, retrospective analysis was to evaluate the safety and efficacy of sacituzumab govitecan in metastatic triple-negative breast cancer (mTNBC) patients managed according to common clinical practice in Italy.MethodsData were retrieved by 7 sites. Triple-negative BC was defined by the lack of expression of estrogen receptor (ER <1%), progesterone receptor (PgR <1%) and human-epidermal growth factor receptor-2 (HER2 0, 1+, 2+ ISH-not amplified)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…There are a few reports in the published literature of SG use in real-world studies in patients with mTNBC. Data from "real-world" French, British, German, Italian, and United States studies have reported outcomes for patients treated with SG in 2L and later lines [15,[17][18][19][20]. Similar to the current study, patients in these real-world studies tended to have poorer performance status and a higher proportion of patients had visceral metastases and central nervous system disease compared with those in the clinical trials [15,[17][18][19][20].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…There are a few reports in the published literature of SG use in real-world studies in patients with mTNBC. Data from "real-world" French, British, German, Italian, and United States studies have reported outcomes for patients treated with SG in 2L and later lines [15,[17][18][19][20]. Similar to the current study, patients in these real-world studies tended to have poorer performance status and a higher proportion of patients had visceral metastases and central nervous system disease compared with those in the clinical trials [15,[17][18][19][20].…”
Section: Discussionsupporting
confidence: 68%
“…Data from "real-world" French, British, German, Italian, and United States studies have reported outcomes for patients treated with SG in 2L and later lines [15,[17][18][19][20]. Similar to the current study, patients in these real-world studies tended to have poorer performance status and a higher proportion of patients had visceral metastases and central nervous system disease compared with those in the clinical trials [15,[17][18][19][20]. In the current analysis, 111 patients were previously treated with a PD-(L)1 inhibitor in the metastatic setting while only 22 had PD-L1 positive results; this may be the result of missingness in the database (70% of patients had an unknown PD-L1 expression status); alternatively, patients may have been positive for microsatellite instability-high and tumor mutational burden-high as pembrolizumab is a preferred treatment for these patients [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of TNBCs primarily includes surgical removal, radiotherapy, and/or chemotherapy, often resulting in side effects and in drug resistance, which diminish the therapeutic potential of many interventions. Despite the wide range of novel treatment approaches currently under investigation, including PARP inhibitors, immune-checkpoint inhibitors, and antibody-drug conjugates (ADCs), additional investigations are necessary to identify TNBC patients who could most benefit from them [13][14][15]. Therefore, it is currently of great interest to identify new strategies adjuvating conventional therapies, and there is increasing consideration of the use of natural substances, due to their potent biological activities and mild side effects [16].…”
Section: Introductionmentioning
confidence: 99%
“…Despite major advancements in its early diagnosis and treatment, conventional therapeutic strategies have shown limitations in effectively treating BC. However, the advent of antibody–drug conjugates, a new class of drug designed to specifically deliver high-potent chemotherapeutic agents directly to cancer cells, has made a breakthrough in the treatment of BC patients 10 12 .…”
Section: Introductionmentioning
confidence: 99%